TPD: A CLOSER LOOK AT TEACHERS' ABILITY IN DEVELOPING PISA-LIKE READING TASKS - Ajeng Meidina Fadhillah, - (2022)
This study is a part of a joint study involving three universities in Indonesia. The bigger study aims to develop a Teacher Professional Development (TPD) program on training teachers to teach PISA-like reading. While the bigger study involved 14 English and 10 Indonesian teachers, this study observed 14 English teachers in developing PISA-like reading tasks. The study has been shaped by the theory of effective TPD (Darling-Hammond, et al. 2017), PISA reading (OECD, 2019a,b), and SFL genre-based approach, especially the type of texts (Macken-Horarik, 2002; Emilia, 2011). A case study design was employed to understand how the training program helped teachers to develop PISA-like reading tasks. The data were obtained from observation of 14 teachers, analysis of PISA-like reading tasks developed by 6 teachers, and interview of 3 teachers. The observation data were analysed based on effective TPD characteristics by Darling-Hammond et al (2017). PISA-like reading tasks developed by teachers which involved; a) text selected by teachers were analysed based on text dimension (OECD 2019a) and b) reading items were analysed based on PISA reading framework on cognitive processes and response format (OECD, 2019a,b). The findings from observation reveal that the training attended the characteristics of effective TPD. The data collected from PISA-like reading tasks developed by teachers indicate that there is an improvement of teachers' ability to select PISA-like texts and to develop PISA-like reading tasks which follow PISA reading framework. Moreover, teachers' responses were likewise positive, indicating their increased awareness of PISA and growth of teachers' ability to develop PISA-like reading tasks are contingent upon the alignment of the TPD program. It is recommended that the training be conducted in a variety of settings with a larger number of teachers to eventually be able to assist Indonesian students in improving their PISA reading literacy. Keywords: PISA, PISA-like reading task, reading, SFL genre-based approach, teacher professional development (TPD)